2016
DOI: 10.1111/clr.12819
|View full text |Cite
|
Sign up to set email alerts
|

The influence of professional competence on the inter‐ and intra‐individual esthetic evaluation of implant‐supported crowns in the anterior maxilla

Abstract: Earlier investigations are confirmed. Width of keratinized mucosa is a risk factor for esthetic predictability of implant-supported crowns in the anterior maxilla in laypersons' ratings. Furthermore, there is an association between the discrepancy of lengths of implant-supported single crowns to their contralateral natural teeth and esthetic satisfaction for all expertise levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…In this case, the difference between the two studies and the present study is probably due to the fact that two first molars were included in the present study, whereas Nickles et al and Rossberg et al did not include any molars. The fact that patients are more satisfied with the outcomes than the clinical parameters might possibly suggest (Petsos, Trimpou, Eickholz, Lauer, & Weigl, ) also seems to apply in this study (CRC: 71.22% vs. 93.33% for minimum satisfied patients). Nevertheless, it can be concluded for both studies that the patients were satisfied with the final results after 10 years.…”
Section: Discussionmentioning
confidence: 54%
“…In this case, the difference between the two studies and the present study is probably due to the fact that two first molars were included in the present study, whereas Nickles et al and Rossberg et al did not include any molars. The fact that patients are more satisfied with the outcomes than the clinical parameters might possibly suggest (Petsos, Trimpou, Eickholz, Lauer, & Weigl, ) also seems to apply in this study (CRC: 71.22% vs. 93.33% for minimum satisfied patients). Nevertheless, it can be concluded for both studies that the patients were satisfied with the final results after 10 years.…”
Section: Discussionmentioning
confidence: 54%
“…This leads to the question: how are professionals' and patients' esthetic evaluations of single tooth implant‐supported crown related ? Only a handful of studies have investigated this and, among these, even less have performed a correlation between the two evaluations ().…”
Section: Relationship Between the Patient's Subjective And The Profesmentioning
confidence: 99%
“…Other authors suggest that the reason why the subjective evaluation is significantly more favorable than the objective evaluation might be related to different perspectives of observation. The patients' self‐assessment is performed using a mirror, whereas the pictures evaluated by dentists had been taken using retractors that held the lips back, forcibly exposing the peri‐implant soft tissues .…”
Section: Relationship Between the Patient's Subjective And The Profesmentioning
confidence: 99%
“…Misje et al, 21 Kourkouta et al, 22 Krenmair et al, 23 and Candel‐Marti et al 24 used the VAS scale. Tymstra et al 25 and Petsos et al, 26 with each using different customized questionnaires (CQ). Tymstra et al 25 used a CQ which comprised of an overall satisfaction score with a numerical range of 0 to 10; 0 = completely dissatisfied , 10 = completely satisfied .…”
Section: Resultsmentioning
confidence: 99%
“…The mean VAS score in Misje et al 21 study was 8.8 out of a possible 10, making the converted PE score 88%. The custom questionnaire (CQ) used by Petsos et al 26 also used a 0 to 10 scale and the mean satisfaction recorded in their study was 8.9 (PE = 89%). Kourkouta et al 22 reported the results of their VAS scale in the form of a median percentage of 95%.…”
Section: Resultsmentioning
confidence: 99%